Arbuscular mycorrhiza and soil microbial interactions in sugarcane agriculture in KwaZuluNatal, South Africa - Jamal-Ally, Sumaiya Faizal (My University, 2013)
A novel holistic approach was used to study the mycotrophic nature of commercial sugarcane varieties grown in KwaZulu-Natal, South Africa. All five varieties were mycotrophic, but N12 had the highest overall mycorrhization and was selected for a pot study to assess the growth response of sugarcane to inoculation with indigenous arbuscular mycorrhizal (AM) fungi and microflora. The pot study suggested that sugarcane will respond positively to inoculation with AM fungi, but the effects are most clear in the early phase of growth and less obvious in later elongation phases. This observation, taken together with the ability of sugarcane to grow well in sterile soil without microflora additions suggests that the plant may be facultatively mycotrophic. A multivariate analysis determined the nutrient relationships between soil and corresponding leaf nutrient levels on 72 sugarcane field plants, categorised according to either high or low percentage colonisation. Highly colonised plants were found to have more positive nutrient correlations compared to lower percentage colonised plants. AM fungi were identified from spore morphology and associated mycorrhizal bacteria (AMB) were identified by 16s rDNA analysis. Partial molecular identification was conducted using a universal eukaryotic forward NS31 primer and general fungal AM1 primers confirming the spores to be of AM fungi origin. A nested PCR was performed, using the universal fungal primers, NS5 and ITS4, followed by primer combinations to target sequences of specific Glomalean groups. Only partial molecular identification was conducted, as RFLPs were not successfully optimised. DNA from the Acaulospora gerdemannii/Acaulospora trappei group, Glomus occultum/Glomus brasilianum group, Glomus mosseae/Glomus intraradices group, Glomus etunicatum/ Glomus clariodeum group and Acaulosporaceae sensu stricto were detected, indicating AM fungi diversity. Bacteria, Brevibacillus reuszeri isolated from Scutellospora nigra, Bacillus megaterium and Stenotrophomonas maltophilia isolated from Glomus geosporum, Paenibacillus chitinolyticus and Bacillus cereus isolated from Acaulospora mellea and Gigaspora margarita spores respectively, were tested for biocontrol capability against pathogenic nematodes of Paratrichodorus, Meloidogyne and Pratylenchus genera. Meloidogyne was the least susceptible to associated mycorrhizal bacteria biocontrol and Paratrichodorus the most susceptible. These studies have contributed to understanding the role of AM in sugarcane agriculture in South Africa. Keywords: arbuscular mycorrhiza, sugarcane varieties, multivariate analysis, nutrient relationships, associated mycorrhizal bacteria, biocontrol, nematodes
A Thesis, submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2013
Keywords: Mycorrhizas.; Soil microbiology.; Sugarcane - South Africa - KwaZulu-Natal.